Radiation protection in newer medical imaging techniques: PET/CT - International Atomic Energy Agency (International Atomic Energy Agency, 2014)
This safety report reviews radiation protection issues arising from the use of positron emission tomography (PET) and computed tomography (PET/CT) and offers guidance on dose management and optimization. It provides data on patient dose and risk levels, as well as information for practitioners on optimizing techniques.